Ask Question
24 January, 03:57

Use geometric model to factor x2+3x+2

0
Answers (2)
  1. 24 January, 04:14
    0
    -1 and - 2

    Step-by-step explanation:

    x ²+3x+2 = 0

    We can solve the expression by first factorizing.

    Factorizing by splitting the middle term

    we look for 2 numbers that when multiplied will be + 2 and when added it will be + 3+2 and + 1 = + 3 and 2 (these is correct because it is the same as the question asked)

    -2 and - 1 = - 3 and 2

    x²+2x+x+2 = 0

    x (x+2) + 1 (x+2) = 0

    (x+1) (x+2) = 0

    x+1 = 0 x+2=0

    x = - 1, x = - 2

    x = - 1 and - 2
  2. 24 January, 05:00
    0
    -1 and - 2

    Step-by-step explanation:x ²+3x+2 = 0

    x²+2x+x+2 = 0

    x (x+2) + 1 (x+2) = 0

    (x+1) (x+2) = 0

    x+1 = 0 x+2=0

    x = - 1, x = - 2

    x = - 1 and - 2
Know the Answer?
New Questions in Mathematics